Advances in Cryptology - ASIACRYPT 2010 16th International Conference on the Theory and Application of Cryptology and Information Security, Singapore, December 5-9, 2010. Proceedings - Abe, Masayuki. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 16th International Conference on the Theory and Application of Cryptology and Information Security, ASIACRYPT 2010, held in Singapore, in December 2010. The 35 revised full papers presented were carefully reviewed and selected from 216 submissions. The papers are organized in topical sections on hash attacks; symmetric-key cryptosystems; block and stream ciphers; protocols; key exchange; foundation; zero-knowledge; lattice-based cryptography; secure communication and computation; models, notions, and assumptions; and public-key encryption.